Lysosome Associated Protein Transmembrane 4B-24 Is the Predominant Protein Isoform in Human Tissues and Undergoes Rapid, Nutrient-Regulated Turnover - Zhou, Kecheng; Dichlberger, Andrea; Ikonen, Elina; Blom, Tomas (The American journal of pathology, 2020)
Studies of lysosome associated protein transmembrane 4B (LAPTM4B) have mainly focused on the 35-kDa isoform and its association with poor prognosis in cancers. Here, by employing a novel monoclonal antibody, the authors found that the 24-kDa LAPTM4B isoform predominated in most, both healthy and malignant, human cells and tissues studied. LAPTM4B-24 lacks the extreme N-terminus and, contrary to LAPTM4B-35, failed to promote cell migration. The endogenous LAPTM4B-24 protein was subject to rapid turnover with a t1/2 of approximately 1 hour. The protein was degraded by both lysosomal and proteasomal pathways, and its levels were increased by the availability of nutrients and lysosomal ceramide. These findings underscore the pathophysiological relevance of the LAPTM4B-24 isoform and identify it as a dynamically regulated effector in lysosomal nutrient signaling.